Effect of sleeve length on deformation properties of grouted splices - Feng Lin; Xiaobao Wu (Građevinar, 2017)
Tests on 12 grouted splices were performed to investigate their deformation properties under tensile loading. Test variables included diameter and type of spliced bars and the size of splicing sleeves. Finite element method based models of the splices were built, verified and used to investigate the effect of sleeve length on the deformation properties of the grouted splices. The sleeve length significantly affected the failure modes and further affected the splices’ deformation properties. A recommendation was proposed to maximize deformation properties of a specific splice by using a critical sleeve length associated with failure mode of bar fracture.